Identification by molecular diagnosis of mosaic Turner's syndrome in an obligate carrier female for fragile X syndrome. Issue 1 (January 1994) - Tejada, M I; Mornet, E; Tizzano, E; Molina, M; Baiget, M; Boue, A
Abstract : A case of mosaic Turner's syndrome with a 45, X/46, XX/47, XXX karyotype, who was also a fragile X obligate carrier as the mother of an affected boy, was identified by molecular diagnosis. Complete haplotyping and direct DNA analysis showed that the X chromosome in all metaphases was the normal X. At the age of 57, she is mentally normal. Her external appearance was typical of Turner's syndrome. This report shows that molecular studies in conjunction with cytogenetic analysis can help in the clinical diagnosis of a rare case and can show the uniqueness of a case such as the one here described.